Sport-related concussion evaluation and management - Doperak, J.; Anderson, K.; Collins, M.; Emami, K. (Clinics in Sports Medicine, 2019)
Concussion is a challenging and controversial medical diagnosis that can test even the most seasoned practitioner. Knowledge on this topic is ever evolving. It was not so long ago that grading guidelines were based on loss of consciousness and amnesia. Medicine has seen a renaissance of discovery over the past 20 years in concussion evaluation and management. A PubMed search for "concussion" between 1990 and 2000 produced just over 1000 articles and that same search including the last 18 years expands to over 10,000 publications. The most recent knowledge and recommendations are discussed based on the published evidence.